Pengaruh Transformational Leadership Terhadap Disiplin Kerja Petugas di Lembaga Pemasyarakatan Kelas IIB Klaten - Fatimah Rahman (Jurnal Ilmiah Poli Bisnis, 2021)
leadership and work discipline is a unity that must be owned by correctional officers. These two aspects have an impact on the performance of officers in prisons. This scientific article was created study to explain the transformational leadership influence on the work discipline of officers in The Correctional Institution Class IIB Klaten. Researchers used quantitative methods. Research instruments in the form of questionnaires with a Likert scale that has previously been conducted validity and reliability tests. Population as well as research sample as many as 85 respondents. The data obtained was analyzed using parametric statistics, which is a spss 20 application-assisted t test. The results of this study indicate that all coefficients of positive value with regression equations namely Y = 0.301 + 0.970X that can be stated that transformational leadership affects the discipline of the officer's work positively and significantly with the direction of exchange that is directly proportional to the coefficient X that is positive value. The coefficient of determination or R square (r2) obtained from the results of this study amounted to 0.716. The results explained that transformational leadership variables have an influence and explain the work discipline variable by 71.6%. The results of this research are expected to be information as well as considerations to optimize leadership skills and discipline in working for prison officers in Indonesia.